(untitled) (Филолошке студије, 2019)
The situation described in a sentence is presented by the verb and its actants. One of the central categories is connected with the definiteness or indefiniteness of the main actant, or the actor. In that respect it is accustomed to distinguish the following kinds of sentences: definite personal, indefinite personal, generally personal and impersonal ones. But the definiteness and indefiniteness of the actor can be of two kinds – either formal (grammatical), or functional.